PELATIHAN SIKLUS AKUNTANSI DI SMU RICCI I JAKARTA BARAT - Chelsya; Patricia, Virginia; Fernanda, Vira (Jurnal Serina Abdimas, 2023)
ABSTRACT Education for high school students at Ricci I is part of community service held by lecturers and students at Tarumanagara University with the aim of providing and establishing accounting knowledge for students in order to continue their education. This program contributes to providing accounting knowledge regarding the accounting cycle. The problem that school faces was there is no Accounting Subject in school curriculum, that cause the Accounting knowledge of the students are very low. The presentation of material accounting cycle was online using Zoom Meeting. The result of this presentation for high school students was to gain basic knowledge about how to implement accounting from transaction into financial statement based on the knowledge about accounting cycle.The result was shown in the pre test quiz and post test quiz for the students regarding Accounting knowledge. The material discussed includes various theories regarding accounting cycle as well as practice questions to make students easily understand the material. After this training, writers expect the student of Ricci I will have better provision in facing further education in higher level education. ABSTRAK Pelatihan edukasi kepada siswa/i di SMU Ricci I merupakan bagian dari Pengabdian Kepada Masyarakat (PKM) yang diadakan oleh dosen dan mahasiswa Universitas Tarumanagara dengan tujuan memberikan dan meningkatkan pengetahuan bagi siswa/i untuk melanjutkan pendidikan. Program pelatihan ini berkontribusi untuk memberikan pengetahuan mengenai siklus akuntansi. Permasalahan yang dihadapi mitra adalah tidak adanya mata pelajaran Akuntansi di kurikulum sekolah SMU Ricci I sehingga menyebabkan rendahnya tingkat pengetahuan terkait Akuntansi. Penyampaian materi mengenai siklus akuntansi dilakukan secara daring melalui Zoom Meeting. Hasil dari pelatihan ini bagi siswa/i adalah siswa/i memperoleh pengetahuan mengenai bagaimana proses akuntansi mulai dari transaksi sampai dengan laporan keuangan melalui pelatihan siklus akuntansi. Hasil tersebut terlihat dari hasil pre test dan post test terkait siklus akuntansi berupa quiz sebelum dan sesudah pelatihan siklus akuntansi. Materi yang dibahas juga mencakup berbagai teori mengenai siklus akuntansi disertai dengan soal latihan yang diharapkan memudahkan siswa/i untuk memahami materi yang diberikan. Setelah pelatihan ini diharapkan siswa/i SMU Ricci I memiliki bekal pengetahuan untuk menghadapi jenjang pendidikan lanjut di perguruan tinggi.